2019
DOI: 10.1002/hed.25754
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTP1 and ERCC1 polymorphisms with toxicity in locally advanced head and neck cancer platinum‐based chemoradiotherapy treatment

Abstract: Background Platinum‐based chemoradiotherapy (CRT) is the standard treatment for locally advanced head and neck squamous‐cell carcinomas (HNSCC), and most patients experience serious toxicities. The aim of this study was to investigate the association between candidate genes involved in radiation/platinum pathways and acute toxicity of CRT to determine the predictive value of these polymorphisms for toxicity. Methods Thirty‐six selected single nucleotide polymorphisms (SNPs) in 29 genes were genotyped in 110 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In the literature, there have been several ERCC1 SNPs examined for their cancer risk and s11615 and rs3212986 have been the most frequently studied. For example, identifying the ERCC1 rs11615 genotype may help in predicting a positive or poor outcome of platinum-based chemotherapy for patients with colorectal (29), advanced gastric (30-32) and breast cancer (33) as well as testicular germ cell tumors (34), ovarian (35,36), esophageal (37), and most importantly, non-small cell lung cancer (17)(18)(19)(20). Molecular studies consistently provided evidence showing that ERCC1 rs11615 T allele is associated with relatively lower expression of ERCC1 at both the mRNA and protein levels; however, its role as a predictive marker for cancer therapy is controversial (38-42).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there have been several ERCC1 SNPs examined for their cancer risk and s11615 and rs3212986 have been the most frequently studied. For example, identifying the ERCC1 rs11615 genotype may help in predicting a positive or poor outcome of platinum-based chemotherapy for patients with colorectal (29), advanced gastric (30-32) and breast cancer (33) as well as testicular germ cell tumors (34), ovarian (35,36), esophageal (37), and most importantly, non-small cell lung cancer (17)(18)(19)(20). Molecular studies consistently provided evidence showing that ERCC1 rs11615 T allele is associated with relatively lower expression of ERCC1 at both the mRNA and protein levels; however, its role as a predictive marker for cancer therapy is controversial (38-42).…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation-induced DNA damage leads to cellular responses including DNA damage response, apoptosis, immune response, inflammation, and cell-cycle arrest. Consequently, genetic variability in these signalling pathways could influence radiosensitivity, and in turn could be associated with acute and late toxicity [ 29 32 ]. As a central element in these pathways, it is plausible that NF- κ B activation is associated with radiation-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Soares et al [26] studied the relationship between ERCC1 rs3212986 polymorphism and clinical side effects of chemotherapy and radiation for cervical cancer and reported a link between this gene and the late gastrointestinal toxicity onset. In addition, previous studies have shown the correlation between the ERCC1 status and toxicity and patient-reported quality of life [27].…”
Section: Effects Of Ccl4 and Art On Testicular Histologymentioning
confidence: 96%